Heparin suppresses the induction of c-fos and c-myc mRNA in murine fibroblasts by selective inhibition of a protein kinase C-dependent pathway. - Wright, T C (1989)
Heparin is a complex glycosaminoglycan that inhibits the proliferation of several cell types in culture and in vivo. To begin to define the mechanism(s) by which heparin exerts its antiproliferative effects, we asked whether heparin interferes with the expression of the growth factor-inducible protooncogenes c-fos and c-myc. We show that heparin suppressed the induction of c-fos and c-myc mRNA by serum in murine (BALB/c) 3T3 fibroblasts. Using purified mitogens, we further show that suppression was most marked when protooncogene expression was induced by phorbol 12-myristate 13-acetate, an activator of protein kinase C. By contrast, there was little or no suppression when the cells were stimulated by epidermal growth factor, which, in these cells, utilizes a protein kinase C-independent pathway for the induction of gene expression. Heparin also inhibited the change in cell morphology induced by the phorbol ester but had no effect on the morphological change induced by epidermal growth factor and agents that raise intracellular cAMP. Heparin did not inhibit intracellular protein kinase C activity, phorbol ester-induced down-regulation of protein kinase C, or phosphorylation of the 80-kDa intracellular protein kinase C substrate. These results suggest that heparin inhibits a protein kinase C-dependent pathway for cell proliferation and suppresses the induction of c-fos and c-myc mRNA at a site distal to activation of the kinase.